High serum leptin levels in depressive disorders with atypical features - Gecici, O; Kuloglu, M; Atmaca, M; Tezcan, AE; Tunckol, H; Emül, HM; Ustundag, B (Blackwell Publishing, 2005)
Leptin is thought to be related to vegetative symptoms of depression such as alterations in food intake and weight. Fifty-seven drug-free patients and 26 healthy controls were enrolled in this study. We have found that the serum leptin levels were higher in patients with atypical depressive disorder than in controls, but not in patients with nonatypical depressive disorder, however, body mass index, age, and gender were not significantly different between these groups. Probably, these findings seem to be associated with some features of the atypical depressive disorders such as weight gain, a result of hyperphagia.
Keywords: atypical feature; body mass index; depression; leptin; weight gain